Cellular dsRNA interactome captured by K1 antibody reveals the regulatory map of exogenous RNA sensing - JinA Lim; Namseok Lee; Seonmin Ju; Jeesoo Kim; Subin Mun; Moonhyeon Jeon; Yong-ki Lee; Seok-Hoon Lee; Jayoung Ku; Sujin Kim; Sangsu Bae; Jong-Seo Kim; et al. (Communications Biology, 2025)
Abstract RNA-binding proteins (RBPs) provide a critical post-transcriptional regulatory layer in determining RNA fate. Currently, UV crosslinking followed by oligo-dT pull-down is the gold standard in identifying the RBP repertoire of poly-adenylated RNAs, but such method is ineffective in capturing RBPs that recognize double-stranded RNAs (dsRNAs). Here, we utilize anti-dsRNA K1 antibody immunoprecipitation followed by quantitative mass spectrometry to comprehensively identify RBPs bound to cellular dsRNAs without external stimulus. Notably, our dsRNA interactome contains proteins involved in sensing N6-methyladenosine RNAs and stress granule components. We further perform targeted CRISPR-Cas9 knockout functional screening and discover proteins that can regulate the interferon (IFN) response during exogenous RNA sensing. Interestingly, most dsRBPs promote IFN-β secretion in response to dsRNA stimulation and act as antiviral factors during HCoV-OC43 infection. Our dsRNA interactome capture provides an unbiased and comprehensive characterization of putative dsRBPs and will facilitate our understanding of dsRNA sensing in physiological and pathological contexts.